Various Clinical Manifestations of Congenital Adrenal Hyperplasia in Children - Ayesha Mukhtar, Rabia Munir, Sidra Tul Mun Tha, Javaria Amil, Saima Rasheed, Muhammad Faisal Javaid (Pakistan Journal of Medical & Health Sciences, 2022)
The study’s objectives was to determine the frequency of various clinical manifestations of congenital adrenal hyperplasia in children. Materials & Methods: The research methodology is descriptive and cross sectional. The event was held at the Department of Pediatric Medicine at DHQ Hospital in Faisalabad. The study will last from September 29th to March 28th, 2019. A total of 90 children with congenital adrenal hyperplasia of age 0-10 years of either gender were included. After taking informed written consent from all children’s parents, different clinical presentations (ambiguous genitalia, simple virilising and salt wasting) were noted in each patient. Results: Mean age of children was 4.84 ± 1.78 years. Out of the 90 patients, 62 (68.89%) were male and 28 (31.11%) were females with male to female ratio of 2.2:1. Mean duration of symptoms was 5.79 ± 2.59 days. In this study, I have found the ambiguous genitalia in 27 (30.0%), simple virilising in 17 (18.88%) and salt wasting in 59 (65.56%) children with congenital adrenal hyperplasia. Conclusion: This study has shown that the salt wasting is the most common clinical presentations of congenital adrenal hyperplasia in children followed by ambiguous genitalia and simple virilising. Keywords: Congenital adrenal hyperplasia, ambiguous genitalia, salt wasting.